ENT300 Escape From Reality Spa / Sofea Jinab Anak Juty... [et.al] - Juty, Sofea Jinab; Ismail, Senoritha Sendie; Tanjong, Jenie Jenah; Johnny, Decoline Delone; Peter, Sandra (2015)
The business plan of Escape Reality Pedicure and Manicure nails Spa is proposed so that it can be taken by comprehensive manner. This business plan gives us the opportunity to asses on business world which is it will be one of the main attractive in Kota Samarahan, Kuching after this business being operate. We decided to form partnership business which is we can spend our interest in Nails Spa industry.